Are we there yet? The Murray-Darling Basin and sustainable water management. (February 2019) - Pittock, Jamie
In 2007, then Australian Prime Minister Howard said of the Murray-Darling Basin's rivers that action was required to end the 'The tyranny of incrementalism and the lowest common denominator' governance to prevent 'economic and environmental decline'. This paper explores the management of these rivers as an epicentre for three key debates for the future of Australia. Information on biodiversity, analyses of the socio-ecological system, and climate change projections are presented to illustrate the disjunction between trends in environmental health and the institutions established to manage the Basin sustainably. Three key debates are considered: (1) conflict over the allocation of water between irrigated agriculture versus a range of other ecosystem services as the latest manifestation of the debate between adherents of the pioneering myth versus advocates of limits to growth in Australia; (2) cyclical crises as a driver of reactive policy reform and the prospects of the 2008 Water Act forming the basis of proactive, adaptive management of emerging threats and opportunities; and (3) subsidiarity in governance of the environment and natural resources in the Australian federation. Implementation of the 2012 Basin Plan as promised by the Federal Government 'in full and on time' is a key sustainability test for Australia. Despite Australian claims of exceptionalism, the Murray-Darling Basin experience mirrors the challenges faced in managing rivers sustainably and across governance scales in federations around the world.